An Intelligent, multi-transducer signal conditioning design for manufacturing applications. (October 2017) - Sillitoe, I.; Button, M.; Owhonda, E.
Abstract: This paper describes a flexible, intelligent, high bandwidth, signal conditioning reference design and implementation, which is suitable for a wide range of force and displacement transducers in manufacturing applications. The flexibility inherent in the design has allowed more than 10 specialised transducer conditioning boards to be replaced by this single design, in a range of bespoke mechanical test equipment manufactured by the authors. The board is able to automatically reconfigure itself for a wide range of transducers and calibrate and balance the transducer. The range of transducers includes LVDT, AC/DC strain gauge and inductive bridges, and a range of standard industrial voltage current interface transducers. Further, with a minor low-cost addition to the transducer connector, the board is able to recognise the type of transducer, reconfigure itself and store the calibration data within the transducer, thereafter allowing a plug-and-play operation as transducers are changed. The paper provides an example of the operation in typical manufacturing test application and illustrates the stability and noise performance of the design. Highlights: A flexible multi-transducer signal conditioning design is proposed. The design is able to automatically recognise, configure and balance a wide range of industrial transducers and sensors. Extended performance tests also show improvements in thermal drift and signal to noise ratio.